Dandy-Walker Malformation Presenting with Psychological Manifestations - Yasodha Maheshi Rohanachandra; Dulangi Maneksha Amerasinghe Dahanayake; Swarna Wijetunge (Case Reports in Psychiatry)
Dandy-Walker malformation, which is a congenital malformation of the cerebellum, is documented in literature to be associated with psychotic symptoms, obsessive compulsive symptoms, mood symptoms, hyperactivity, and impulsive behavior. The pathogenesis of psychiatric symptoms in Dandy-Walker malformation is thought to be due to disruption of the corticocerebellar tracts, resulting in what is known as cerebellar cognitive affective syndrome. We present a case of Dandy-Walker malformation presenting with psychiatric symptoms. This case highlights the necessity to be aware of psychiatric manifestations of cerebellar disease as it has an impact on the diagnosis and treatment.